2012
DOI: 10.1100/2012/975971
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Image-Guided Biopsies with a High Detection Rate of Prostate Cancer

Abstract: Aim. To explore the potential of transrectal magnetic resonance image- (MRI-) guided biopsies of the prostate in a patient cohort with prior negative ultrasound guided biopsies. Patients and Methods. Ninety-six men with suspected prostate cancer underwent MRI-guided prostate biopsies under real-time imaging control in supine position. Results. Adenocarcinoma of the prostate was detected in 39 of 96 patients. For individual core biopsies, MRI yielded a sensitivity of 93.0% and a specificity of 94.4%. When stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…These data are comparable to the results of Engehausen et al [14]. In the latter study, 10.4 % of cancers were missed using MRGB, assuming that these carcinomas were already present at the time of MRI intervention and were not de novo neoplasias [14]. The follow-up period was three years in our study.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…These data are comparable to the results of Engehausen et al [14]. In the latter study, 10.4 % of cancers were missed using MRGB, assuming that these carcinomas were already present at the time of MRI intervention and were not de novo neoplasias [14]. The follow-up period was three years in our study.…”
supporting
confidence: 91%
“…Hence, the detection rate for clinically significant cancer in our study is 100 %. This is in accordance with and even higher than observed in the review of the literature [12,14,15,18,19,29]. This emphasizes the capability of MRGB to diagnose clinically significant cancer in patients after negative TRUS.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Another out-of-bore approach uses the MR imaging in a cognitive manner, with the operator interpreting the previously acquired MR imaging information either as reported or by direct visualization and then performing a transrectal US sampling directed to the cognitively recalled locations (28). The transrectal MR imaging-guided biopsy studies (32)(33)(34)(35)(36)(37)(38)(39)(40) report cancer positivity rates of 8%-59%. Puech et al (41) compared cognitive and fusion techniques, showing no significant differences in biopsy yield.…”
Section: Discussionmentioning
confidence: 99%
“…Selected studies have found higher rates of cancer detection with MRI‐guided biopsy than with TRUS‐guided biopsy . Nevertheless, when Moore et al .…”
Section: Applications Of Mri In the Detection Of Prostate Cancermentioning
confidence: 99%